Histopathological Study on Poultry Enteritis in Azerbaijan Province of Iran - Daryoush, Mohajeri; Yousef, Doustar; Mehrdad, Nazeri (International Journal of Poultry Science, 2011)
In this survey, for morphohistopathological study of the enteritis in fowls, 70 specimens of pathologic intestinal lesions were randomly collected from necropsied fowls with the signs of enteritis from different flocks at Tabriz poultry clinics in a course of 6 months. They subjected to detail morphological and histological studies. Epidemiologically, the prevalence of the various kinds of enteritis in association with age, strain and sex was evaluated. One-sample chi-square test, revealed that the highest rate of occurrence (78.57%), belonged to broilers (p